2018
DOI: 10.1007/s00109-018-1680-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of adenosine receptor A3 results in articular cartilage degeneration

Abstract: Adenosine receptor A3 (A3) knockout results in progressive loss of articular cartilage in vivo. Ablation of A3 results in activation of matrix degradation and cartilage hypertrophy. A3 agonists downregulate RUNX2 and CaMKII expression in osteoarthritic human articular chondrocytes. A3 prevents articular cartilage matrix degradation induced by inflammation and osmotic fluctuations. A3 agonist inhibits proteolytic activity of cartilage-degrading enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
4
13
0
Order By: Relevance
“…The anti-inflammatory properties of stimulating both adenosine receptors 28 likely www.nature.com/scientificreports/ play a critical role in preventing progression of osteoarthritis in these models, particularly the monoiodoacetateinduced model of osteoarthritis which is characterized by acute inflammatory changes. Both A2AR and A3R stimulation inhibit chondrocyte production of catabolic proteins 11,14,27,29,30 associated with cartilage destruction but, to date, only A2AR stimulation of chondrocytes induces production of cartilage matrix, as shown here.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The anti-inflammatory properties of stimulating both adenosine receptors 28 likely www.nature.com/scientificreports/ play a critical role in preventing progression of osteoarthritis in these models, particularly the monoiodoacetateinduced model of osteoarthritis which is characterized by acute inflammatory changes. Both A2AR and A3R stimulation inhibit chondrocyte production of catabolic proteins 11,14,27,29,30 associated with cartilage destruction but, to date, only A2AR stimulation of chondrocytes induces production of cartilage matrix, as shown here.…”
Section: Discussionsupporting
confidence: 62%
“…Although it is likely, based on the efficacy of the lipo-CGS21680 (a selective A2AR agonist) treatments to promote cartilage formation, that stimulation of the A2AR is principally responsible for the improvement in osteoarthritis observed here it is possible that other adenosine receptors are also involved in this therapeutic effect. Deletion of both A2AR and A3R have been shown to lead to osteoarthritis 11,27 and it is likely that the homeostatic role of adenosine in cartilage and chondrocytes is mediated by both receptors. Interestingly osteoarthritis becomes evident within 6 months of age in A2AR deficient mice but has only been described in aged mice lacking A3R, suggesting that the A2AR is more critical for maintenance of chondrocyte homeostasis throughout life, whereas loss of the A3R exacerbates the effects of age on cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…The replacement of adenosine in the intraarticular space has shown delayed osteoarthritis progression in a rat model of post-traumatic osteoarthritis through a molecular mechanism involving A2A adenosine receptor activation (Corciulo et al, 2017). We also demonstrated that mice lacking A2A adenosine receptors develop spontaneous bone and cartilage features of OA associated with reduced motor activity and Shkhyan and colleagues demonstrated that ablation of A3 receptors results in OA development in aged mice (Corciulo et al, 2017;Shkhyan et al, 2018) (Figure 3).…”
Section: P1 Receptorssupporting
confidence: 54%
“…A3R knockout (KO) mice develop progressive loss of articular cartilage. Agonists for A3R downregulate key genes implicated in OA pathology, such as RUNX2 ( 151 ). In a recent study CF101, a highly selective A3R agonist, was orally administered twice daily to monosodium iodoacetate OA-induced rats.…”
Section: Purinergic System In Oa and Modulation By Metainflammationmentioning
confidence: 99%
“…In the case of excessive joint motion, which leads to excessive activation of CD73 via hypoxia inducible factor (HIF)-1α, extracellular adenosine accumulates. The consequent activation of the low-affinity A2BR seems to play a harmful role in cartilage homeostasis, possibly due to its capacity of stimulating inflammatory pathways involving MAPK ( 128 , 151 ). In OA, as a low-grade chronic inflammatory disease, increased extracellular adenosine levels may switch selectivity of receptor binding toward A2BR, generating hyperalgesia ( 138 ) ( Table 2 ).…”
Section: Purinergic System In Oa and Modulation By Metainflammationmentioning
confidence: 99%